Speech teams of wrestling at the European Nations Cup 2015 - Pavel Panov; Yurij Tropin; Viktor Ponomaryov; Sergey Beletskiy (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to analyze the performance of national teams of wrestling at the European Nations Cup in 2015. Material and Methods: the analysis of 208 wrestlers highly. Results: determined that, among other factors, the advantage of the strongest wrestlers is successful and stable use of technical and tactical actions during the fight and the ability to impose his opponent style of fighting. Conclusions: it was found that in the competitive technology dominated the offensive, the fight is ongoing at a fast pace, techniques are performed after prior training and if the athlete is confident that the reception will be executed